PTH-120 Coeliac Disease And Double-balloon Enteroscopy: What Can We Achieve? The Experience Of Two European Tertiary Referral Centres. (9th June 2014) - Mooney, PD; Tomba, C; Branchi, F; Sanders, DS; Sidhu, R; Locatelli, M; Conte, D; Bardella, MT; Elli, L
Abstract : Introduction: The indications for and efficacy of device-assisted enteroscopy is not standardised in coeliac disease (CD). We present the largest study to date to evaluate the clinical role of double-balloon enteroscopy (DBE) in complicated CD. Methods: DBE findings in CD patients with suspected small bowel complications were retrospectively evaluated in two tertiary referral centres (Milan and Sheffield). Demographic data of the studied cohort were compared with a database of 1000 non complicated CD patients. Results: Findings from 14 oral and seven anal DBE in 19 CD cases (11 males p = 0.003 vs control database) were reviewed. Mean age at CD diagnosis (37 ± 19 vs. 27 ± 18) and at small bowel evaluation (49 ± 15 vs. 38 ± 13) was significantly higher in the DBE group compared to controls (p < 0.001). Indications for DBE were the follow up of known refractory coeliac disease (RCD) (#7), suspicion of small bowel complications due to gastrointestinal symptoms (#4), severe iron deficiency anaemia (#6) and long standing poor dietary adherence (#2). All DBE were performed after small bowel capsule endoscopy, except for one case. 3 patients from the known RCD group had evidence of TCRg monoclonality on biopsy (type 2 RCD). One of these patients had jejunal ulceration whilst the other 2 cases had areas with small white raised patches. A further RCD case had evidence of jejunal ulceration however biopsies didn't show any evidence of TCRg monoclonality. A single RCD case had distally worsening atrophy. Patchy small bowel atrophy was observed in all the non adherent patients and in 2 patients with persistent gastrointestinal symptoms who had only been on a gluten free diet for a short time. Two jejunal adenocarcinomas and an ileal neuroendocrine tumour were detected. All 3 of these patients presented with iron deficiency anaemia. Conclusion: This is the largest international DBE outcomes study in CD patients. Even minor mucosal lesions seen at DBE may be associated with significant pathology. Evaluation of non-responsive/refractory symptoms by DBE was associated with older patients (p < 0.001) and a higher proportion of males (p = 0.003) than an uncomplicated CD population. Further studies are needed to better understand the clinical relevance of the small bowel endoscopic features and to optimise DBE indications. Disclosure of Interest: None Declared.